Leitura literária de lendas indígenas - Ramalho, Sérgio Gonçalves (2020)
This work aims to present a literary reading practice of texts with an indigenous theme in schools in the municipality where the author works as a teacher. It has as general objective to promote a literary reading of indigenous legends to students in their final years of Middle School, as well as to enable these students to learn about indigenous culture through literary reading of legends. The specific objectives are to know the cultural traits of the indigenous people; identify characteristics of the indigenous legends of the Pankararu People; realize the importance of elements of the culture of these indigenous people. Therefore, the relevance of this study is justified, which suggests a pedagogical intervention through a proposal of literary reading of indigenous legends, using as Corpus for the reading and analysis, legends of the Pankararu indigenous people. This research is based on the cultural model of reading by Gomes (2012) that proposes a cultural reading from the interdisciplinary perspective and an inclusive practice of recognition of identities. It is also guided by the subjective reading model proposed by Rouxel (2014), that gives rise to a literary experience that enables the pleasure of reading from the perspective of subjectivity. To contribute to the reflections on memory, we looked for support in the theoretical contribution of Nora (1993) and Candau (2016) among others. As for the concept of legend, as a legacy of the cultural memory of a people, we rely on Bayard (1957), Cascudo (2001) and Witzel (2014). On the history and cultural legacy of the Pankararu people, we look for support in the researches of Mura (2013) and Matta (2009) whose reflections revolve around memory, identity and Pankararu culture. For our methodological proposal for the application of the literary reading practice of indigenous legends, based on expanded sequences, we look for support in suggestions from the expanded sequence proposed by Cosson (2014). The sequences guided the production of a final product: a book of literary reading, whose social function is to potentiate the cultural literacy of the students, while making it possible to bring them closer to the indigenous theme, still marginalized in the school context, as well as didactically instruct teachers to deal with this theme in the classroom.